Perbedaan Tingkat Kecemasan Mahasiswa 2 Semester Terakhir dengan IPK di Bawah 3,50 dan di Atas 3,50 untuk Mencapai Predikat Cum Laude - Puspitasari, Indah; Susilohati, Mardiatmi; Wicaksono, Bagus (Nexus Pendidikan Kedokteran dan Kesehatan, 2013)
Background: One of keys to success during adolescence is determined by the educa-tional achievements. Post-secondary students tend to find ways and reasons to be more advanced and motivated obtaining better achievement than before. At tertiary level education including university, assessment of academic achievements is expressed by Grade Point Average (GPA). Achieving cum laude title when graduated from a university which requires a final GPA of above 3,50 is desirable by many students. This study aim to evaluate the difference of anxiety levels among undergraduate students at final year with GPA below 3,50 and above 3,50 to achieve cum laude title. Methods: The study was an analytical observational study using cross-sectional design, held in July 2012 at Faculty of Medicine, Sebelas Maret University, Surakarta. Samples were selected using purposive sampling method. Samples were then asked to fill in: (1) Curriculum vitae form, (2) L-MMPI questionnaire (to evaluate their thruthfulness in answering questionnaires), (3) T-MAS questionnaire (to measure anxiety scores). Data were analyzed by Kolmogorov-Smirnov normality test and the independent t-test using SPSS 17,0 for Windows. Results: Sixty-six medical students participated in this study. The mean anxiety scores of students with GPA below 3,50 was 21,51 Â± 6,87, as for those with GPA above 3,50 was 18,65 Â± 4,77. Result from independent t-test showed no statistically significant difference of anxiety scores between the two groups (p = 0,118). Conclusion: There was no difference of anxiety levels among final year undergraduate students whose GPA is below 3,50 and above 3,50 in order to achieve cum laude title. Keywords : Anxiety, GPA, cum laude title